Terahertz Switch Utilizing Inorganic Perovskite-Embedded Metasurface - Xiong, Ri-Hui; Peng, Xiao-Qing; Li, Jiu-Sheng (Frontiers in Physics, 2020)
Various applications of terahertz technology require a large number of various terahertz wave control devices. Yet, high efficient and rapid-response terahertz switch is still a great challenge. Here, we introduce a new scheme, based on inorganic perovskite quantum dots (CsPbBr3-QDs) embedded metasurface under different pump laser powers realize terahertz wave high-speed switching performance. The off-on speed of the presented device achieves to be 8MHz. This kind of components provides a new idea and a cost-effective functional solution for manipulating the terahertz waves in emerging terahertz devices and systems.